Importance of circadian rhythms for regulation of the cardiovascular system - studies in animal and man - Lemmer, Björn (28th Annual International Conference of the IEEE Engineering in Medicine and Biology Society, 2006, 2006)
In all mammals the cardiovascular system is highly organised in time. Pathophysiological cardiovascular events also do not occur at random (e.g. sudden cardiac death, stroke, ventricular arrhythmias, arterial embolism, symptoms of coronary heart disease, myocardial infarction). Radiotelemetry allows to get more insight into the circadian regulation of the cardiovascular system in unrestrained freely-moving animals. We monitored by telemetry blood pressure, heart rate (also be ECG-recordings), motility and body temperature in various strains of normotensive and hypertensive rats as well as in wildtype and knock-out mice. Our data gave evidence that the circadian rhythms in blood pressure and heart rate are controlled by the biological clock(s), since in rats and mice the rhythms persisted under free-running conditions in total darkness and were abolished in rats by lesioning of the "master clock" located in the suprachiasmatic nulcei